The Evaluation of Various Restoration Techniques on Internal Adaptation of Composites in Class V Cavities - Dionysopoulos, D.; Papadopoulos, C.; Koliniotou-Koumpia, E. (International Journal of Biomaterials, 2014)
Aim. The aim of this study was to evaluate the effect of different restoration techniques on the formation of internal microgaps between materials and dentin in class V restorations. Materials and Methods. Twenty-five extracted human premolars were prepared with standardized class V cavity outlines (3 mm × 2 mm × 2 mm). The cavities were randomly divided into 5 groups of 10 cavities each and restored according to manufacturer’s instructions: Group 1: preheating (55°C) conventional composite (Filtek Z250), Group 2: flowable composite (Filtek Flow), Group 3: Filtek Flow + Filtek Z250 light-cured separately, Group 4: Filtek Flow + Filtek Z250 light-cured simultaneously, and Group 5 (control): Filtek Z250 at room temperature (23°C). The specimens were then thermocycled and cross-sectioned through the center of the restoration. Subsequently, impressions were taken, and epoxy resin replicas were made. The internal adaptation of the materials to the axial wall was analyzed under SEM. Results. The preheated Filtek Z250 (Group 1) showed better internal adaptation than the room temperature groups (P<0.05). The combination of Filtek Flow with Filtek Z250 which was light-cured separately (Group 3) exhibited better internal adaptation than control group (P<0.05). Conclusion. Different restoration techniques exhibit different behavior regarding internal adaptation to dentin after photopolymerization.